2023
DOI: 10.1139/cjfr-2022-0286
|View full text |Cite
|
Sign up to set email alerts
|

Complex network analysis of global forest products trade pattern

Abstract: Forest products trade has a critical role to play in both global economic development and environmental protection. Based on the trade data of global forest products, raw forest products and processed forest products from 2000 to 2020, this paper constructed a trade network and analyzed its pattern by using indicators such as density, average distance, out-strength and in-strength. The results show that from 2000 to 2020, the global trade network of forest products has been increasingly connected. Compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…In contrast to prior research on SFM by Guan, Xu, and Ip Ping Sheong [14], which explored the effects of FSC CoC certification on international trade, the studies by Chen et al [15] regarding the impact of forest certification on global timber product trade, and Klarić et al [17] who delved deeply into the benefits, motives, and shortcomings of FSC Chain of Custody certification in the wood industry, this research offers a new perspective by analysing the link between FSC CoC certification in Croatia and its wood product exports to the EU over a 21-year period, employing a unique gravity data approach. Furthermore, it integrates findings from other studies [20][21][22][23][29][30][31] that identified key macroeconomic indicators as decisive factors for export values. The use of dynamic panel data analysis further deepens this examination, emphasizing the crucial relationship between forest certification, sustainability, and market acceptance.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…In contrast to prior research on SFM by Guan, Xu, and Ip Ping Sheong [14], which explored the effects of FSC CoC certification on international trade, the studies by Chen et al [15] regarding the impact of forest certification on global timber product trade, and Klarić et al [17] who delved deeply into the benefits, motives, and shortcomings of FSC Chain of Custody certification in the wood industry, this research offers a new perspective by analysing the link between FSC CoC certification in Croatia and its wood product exports to the EU over a 21-year period, employing a unique gravity data approach. Furthermore, it integrates findings from other studies [20][21][22][23][29][30][31] that identified key macroeconomic indicators as decisive factors for export values. The use of dynamic panel data analysis further deepens this examination, emphasizing the crucial relationship between forest certification, sustainability, and market acceptance.…”
Section: Introductionsupporting
confidence: 59%
“…Reviewing the literature related to macroeconomic indicators and exports, several studies [20][21][22][23][24] have shown that traditional macroeconomic indicators (such as nominal GDP, GDP per capita, unemployment, manufacturing value added, real effective exchange rate, and distance between countries) have been identified as significant and crucial determinants that lead to higher export values and stimulate export activities. For instance, Brazil's GDP variable has demonstrated a positive influence on exports of wood product, illustrating that the higher economic growth in a country theoretically corresponds to higher production levels, and consequently, a greater quantity exported [22].…”
Section: Introductionmentioning
confidence: 99%